[OP.2C.07] THE GROWING RATE OF ATRIAL FIBRILLATION AMONG HEART FAILURE PATIENTS IN POLISH PRIMARY HEALTH CARE – DATA FROM 2005 AND 2013. (September 2016) - Rewiuk, K.; Wizner, B.; Fedyk-lukasik, M.; Zdrojewski, T.; Opolski, G.; Dubiel, J.S.; Grodzicki, T.
Abstract : Objective: The aim of this study was to evaluate temporal changes in epidemiology and management of atrial fibrillation (AF) in population of Polish outpatients with heart failure (HF). Design and method: The present study was performed within the framework of two editions of the Polish nationwide heart failure surveys (2005 and 2013), and included patients with HF treated in respectively 400 and 390 primary care centers. Data was collected using questionnaires and included demographic characteristics as well as information about coexisting diseases and treatment, provided by physicians on the basis of the available medical records. Results: The study included 2000 patients in 2005 and 2006 patients in 2013. We observed a significant increase in the incidence of AF in patients with HF between the two surveys (38.4% in 2005 vs 50.4% in 2013, p < 0.001). We also observed some changes in comorbid profile in this group of patients - a decrease in the prevalence of coronary heart disease (78.6% vs 67.8%; p < 0.001), increased incidence of diabetes (30.0% vs 37.8%; p < 0.001), chronic kidney disease (10.3% vs 22.6%; p < 0.001) and anemia (9.4% vs 13.5%; p = 0.008). There has been a change in the pharmacotherapy - a rise in use of beta-blockers (66.5% vs 89.1%; p < 0.001) and angiotensin receptor blockers (1.6% vs 16.8%; p < 0.001) at the expense of digoxin (50.4% vs 26.5%; p < 0.01) and ACE-inhibitors (80.5% vs 67.2%; p < 0.01). We documented a significant increase in the proportion of patients receiving thromboprophylaxis (37.6% vs 67.5%, p < 0.001). Conclusions: The incidence of AF in patients with HF considerably increases. This trend is accompanied by a change of comorbidity towards non-coronary problems. Observed improvement in treatment gives some hope to reverse this disturbing trend, but this requires further observations.